RENCANA PENATAAN LANSKAP DESA WISATA SECARA PARTISIPATIF DI ENSAID PANJANG SINTANG KALIMANTAN BARAT - Janiarto Paradise Pawa; Siti Nurisjah; Soeryo Adiwibowo (Jurnal Lanskap Indonesia, 2014)
Ensaid Panjang village is a rich and unique area in terms of landscape and culture. Dayak cultural preservation in Ensaid Panjang potentially under threat because of the infiltration of foreign culture and land clearing. It is necessary to preserve the culture of Ensaid Panjang. One of the effort is the village planning Ensaid Panjang as a tourist village based on local tradition and culture. This study aims to answer the problems of tourism development planning through participatory approach in the perspective of landscape architecture to create community based plan for sustainable landscape. This research was conducted using a participatory approach using quantitative descriptive method. The method of analysis used participatory mapping to determine the boundaries of the planning area, potential tourism objects and attraction analysis performed by scoring, and the visual quality attractions was conducted by Scenic Beauty Estimation ( SBE ), the analysis of community participation was done with FGD method using matrix scoring techniques. The results showed that Ensaid Panjang has an area 3426,88 ha, consist of sacred zone 2.64 ha (0.07 % ) , natural protection zone 1599 ha (46,67 % ), and utilization zone covering an area of 1825,12 ha (53,26 % ). Potential tourist object and attractions of Ensaid Panjang village consists of cultural objects and attractions in the form of betang house traditional architecture and residential communities, and the potential of nature tourism in the form of hills forest, swamp forest, and natural features such as waterfalls and rivers. Ensaid Panjang community supports tourism development in their village by being a part of the tourist attractions and supporting tourism activities, this activity including villagers as weavers, tour guide, blacksmith, artist, homestay host. The concept plan of development and structuring of tourism villages Ensaid Panjang is "Participatory Rural Tourism Landscape and Cultural Preservation of Dayak Desa." This concept is implemented with the involvement of local communities with emphasis on maximum benefit for the community and the preservation of local culture.